Electroless chemical aging of carbon felt electrodes for the all-vanadium redox flow battery (VRFB) investigated by Electrochemical Impedance and X-ray Photoelectron Spectroscopy. (20th August 2017) - Derr, Igor; Przyrembel, Daniel; Schweer, Jakob; Fetyan, Abdulmonem; Langner, Joachim; Melke, Julia; Weinelt, Martin; Roth, Christina
Abstract: Electroless chemical aging of commercially available, porous carbon felt electrodes for the all-vanadium redox flow battery (VRFB) was investigated by full-cell and half-cell measurements in a beaker set-up and a cell with flow-through geometry at different states of charge and different temperatures. Changes in the charge transfer resistance and the double layer capacitance due to chemical aging were determined by electrochemical impedance spectroscopy (EIS) and correlated with ex-situ X-ray photoelectron spectroscopy (XPS). EIS measurements revealed that the aging of the carbon electrodes was dependent on the temperature for low vanadium concentrations and independent on the temperature for high vanadium concentrations. This indicates that the electroless aging of the electrodes occurs due to a chemical reaction with the sulfuric acid and with the vanadium. XPS measurements revealed an increase of the amount of surface functional groups on the carbon felt electrodes by a factor of 1.5 to 1.8 after 8 days of mere contact with electrolyte. Moreover, the conducting sp 2 -hybridized layer was diminished by a factor of 2 or more. It appears that the negative half-cell [V(II)/V(III)] is more strongly affected by chemical aging than the positive half-cell [V(IV)/V(V)]. Electroless aging was found to be inevitable for all the carbon felts used.